Dimethyl Oxalylglycine Activates Tendon‐Derived Stem Cells to Promote Regeneration of Achilles Tendon Rupture in Rats via HIF‐1α. Issue 3 (9th December 2022) - Wang, Yanmao; Li, Minyao; Lin, Yiwei; Yin, Fuli; Shan, Haojie; Wu, Tianyi
Abstract: Tendon‐derived stem cells (TDSCs) are stem cells found in tendons that may become ideal seed cells for tendon repair. This study aims to investigate whether dimethyl oxalylglycine (DMOG) treatment could effectively improve the regeneration ability of TDSCs to repair Achilles tendon injury. Stem cells of rat Achilles tendon are isolated and treated with DMOG or Lificiguat (YC‐1). The treated TDSCs are transplanted into rats with Achilles tendon injury. A batch of animals is sacrificed every week for biomechanical and historical analyses. The recovery of Achilles tendon is tested by biomechanics and histology. DMOG could activate TDSCs in vitro and improve their differentiation ability by regulating the expression levels of hypoxia‐inducible factor‐1α (HIF‐1α) and early growth response 1 (EGR1). As an inhibitor of HIF‐1α, YC‐1 could weaken the effect of DMOG. TDSCs pre‐treated with either DMOG or YC‐1 are transplanted into rats with Achilles tendon injury, and DMOG pre‐treatment could effectively improve the regeneration of Achilles tendon. In summary, DMOG improves TDSC differentiation ability, and transplanting TDSCs pre‐treated with DMOG into rats with Achilles tendon injury can effectively improve tendon regeneration, which may serve as a novel approach for the treatment of Achilles tendon injury. Abstract : DMOG activates TDSCs in vitro and improves their differentiation ability by regulating the expression levels of hypoxia‐inducible factor‐1α and early growth response 1. DMOG pre‐treatment enhances TDSC differentiation ability. TDSCs pre‐treated with DMOG effectively improve the regeneration of Achilles tendon in the rat model of Achilles tendon injury. DMOG may be used for the treatment of Achilles tendon injury.